Sigmoid Volvulus in An Adolescent Female With Colitis: A Rare Case Report - Jaya Putra, Edwin Satya; Setiawati, Rosy (Talenta Publisher, 2024)
Introduction: Sigmoid volvulus among pediatric patients is a rare occurrence. Case: A 13-year-old pediatric female presented to hospital’s emergency department with abdominal pain, nausea, and inability to defecate for three days. No fever or vomiting was reported. She had a multiple episodes of constipation and was menstruating. Physical examination suggested bowel obstruction. Plain abdominal radiograph showed diffuse colon dilation with minimal small bowel and pelvic gas. Abdominal contrast CT revealed severe large bowel dilatation with redundancy from the cecum to the rectosigmoid area, along with a